A process net model approach for multiple process plans - Park, J.-H.; Kang, M.-H. (Korean Society of Mechanical Engineers, 1998)
A process planning system that generates alternative process plans offers multiple process plans for a part, thereby providing the flexibility to cope with changes in shop floor status. In this paper, we introduce the concept of a process net as a model for the generation of alternative process plans. We also show the usefulness of the process net model in generating alternative process plans by implementing the developed system to construct process nets, and devising an algorithm to generate alternative process plans for rotational parts.